2022
DOI: 10.3389/fmicb.2021.765091
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Indicators Are Ubiquitous Members of Pelagic Microbiome in Anthropogenically Impacted Coastal Ecosystem

Abstract: Coastal zones are exposed to various anthropogenic impacts, such as different types of wastewater pollution, e.g., treated wastewater discharges, leakage from sewage systems, and agricultural and urban runoff. These various inputs can introduce allochthonous organic matter and microbes, including pathogens, into the coastal marine environment. The presence of fecal bacterial indicators in the coastal environment is usually monitored using traditional culture-based methods that, however, fail to detect their un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 143 publications
(218 reference statements)
0
10
0
Order By: Relevance
“…Taken together, our results highlight that, differently from other potential pathogens (Fonti et al 2021 ), members of the Vibrionaceae family retrieved at sea are unlikely to be related to wastewater inputs. Therefore, we suggest to carefully consider the inclusion of the genus Vibrio in the “blacklist” of potentially pathogenic genera in surveys of microbiological pollution in coastal waters (e.g., Paliaga et al 2017 ; Fonti et al 2021 ; Orel et al 2022 ), also in light of the fact that the distribution of pathogenic traits within a single species (e.g., V. parahaemolyticus , V. vulnificus ) carried by specific genes (e.g., tdh , trh , vcgC ) is highly variable (Fabbro et al 2010 ; Nigro et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results highlight that, differently from other potential pathogens (Fonti et al 2021 ), members of the Vibrionaceae family retrieved at sea are unlikely to be related to wastewater inputs. Therefore, we suggest to carefully consider the inclusion of the genus Vibrio in the “blacklist” of potentially pathogenic genera in surveys of microbiological pollution in coastal waters (e.g., Paliaga et al 2017 ; Fonti et al 2021 ; Orel et al 2022 ), also in light of the fact that the distribution of pathogenic traits within a single species (e.g., V. parahaemolyticus , V. vulnificus ) carried by specific genes (e.g., tdh , trh , vcgC ) is highly variable (Fabbro et al 2010 ; Nigro et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Northern Adriatic Sea is also exposed to various anthropogenic impacts such as different types of wastewater pollution and agricultural and urban runoff. These inputs can introduce allochthonous organic matter and microbes into the environment (Orel et al, 2021). It is reported that the abundance, composition, and activity of microbial communities in this area depend, to a large extent, on river discharges (Celussi et al, 2010;Mozetič et al, 2012), and the Northern Adriatic Sea receives significant freshwater inputs from several rivers, such as Adige, Brenta, Piave, and Po, along the northwestern coast of Italy.…”
Section: Introductionmentioning
confidence: 94%
“…Multidrug-resistant bacteria and antibiotic resistance genes have been used as indicators of contamination in various water environments, such as coastal waters (Shinde et al, 2020;Orel et al, 2022;Zhao et al, 2022), rivers (Niestępski et al, 2020;Odubanjo et al, 2021;Allsing et al, 2022), or localised water environment, such as ponds, lakes or karsts (Stange and Thiem, 2020;Hou et al, 2021;Kalinowska et al, 2021;Zhang Y et al, 2021). Tarek and Garner (2023) proposed a framework for the identification of indicator genes with the objective of monitoring antibiotic resistance in wastewater.…”
Section: Ra-relevant Genes Within the Environmental Microbiomementioning
confidence: 99%